Reinventing the bicycle: how calculative practices shape urban environmental governance. Issue 3 (4th May 2017) - Jensen, Jens Stissing; Cashmore, Matthew; Elle, Morten
ABSTRACT: The concept of sustainability transitions has become increasingly prominent in academic and policy discourses during recent decades, but the importance of the link between knowledge-producing epistemic practices and urban governance has been underappreciated in this discourse. Based on a case study of cycling in Copenhagen between 1900 and 2015, and drawing upon a governmentality-inspired analytical framework, this research demonstrates that transformative governance may be initiated by epistemic practices that render urban systems visible in other ways. Urban cycling has been reconstructed over time in Copenhagen as a traffic safety 'problem', a component of the experiential and liveable city, and a health-producing (and hence economically valuable) regional transport mode. The research findings emphasise that epistemic practices can provide a powerful stimulus for creating changes in urban governance. The results also provide support for initiatives to broaden the terms of academic debate on sustainability transitions.